Perancangan Personalized Furniture dengan Menggunakan Sistem Modular untuk Tempat Tinggal di Surabaya - Chintya Dhefie Djajapurnama; Grace Mulyono (Intra, 2018)
This design research has been performed in order to cater to the needs of users for personalized furniture that can adapt to the function desired by a variety of different users. Using production waste material from mango and acacia wood as the main materials, this design aims to prioritize efficiency in the use and production processes of the furniture industry.The methodology used for data collection and design compilation is the Design Thinking method, consisting of problem analysis, problem solving, design concept, design solution and application.The final result is documented through construction drawings and visualization in the form of furniture sets. Finally, the furniture is also equipped with branding attributes designed by the author for marketing purposes.